Material strength at high pressure - Lonsdale, C. M.; McHardy, J. D.; Storm, C. V.; Roy, C. R.; MacLeod, S. G.; McMahon, M. I. (Cranfield University Defence and Security, 2024)
Over the past 30 years, advancements in the focusing schemes, beam quality, and X-ray brilliance at synchrotron light sources have enabled the reduction of X-ray beam dimensions from tens of micrometers into the sub-micrometer domain. These developments have enabled spatial mapping of the stress state at multi-megabar pressures in the diamond anvil cell. This work presents angle-dispersive X-ray diffraction results collected on beamline P02.2 at the Petra-III synchrotron using a beam size (FWHM) of 0.85 x 0.85 microns on an Ir sample. Variations in the local stress state in the sample were analysed through two approaches based on X-ray diffraction peak shifting and broadening. The results of the two methods are compared and highlight the effectiveness of Bi as a pressure transmitting medium, even at multi-megabar pressures. We look to apply these techniques to future experiments into obtaining more precise investigations of phase transitions and material strength at extreme pressure.
Keywords: High Pressure; Diamond Anvil Cells; Material Strength; Stress State; Diffraction Mapping